2018
DOI: 10.20944/preprints201811.0417.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis, Characterization and Anti-Microbial Activity of <em>Citrus limon</em> Mediated Nanoparticles

Abstract: Previously the nanoparticles were synthesized by chemical methods which were costly 15 and toxic to bio-systems. Plant extracts provides simpler, eco-friendly and cost efficient method for 16 synthesizing nanoparticles. Lemon peel extract (LPE) was used to synthesize silver nanoparticles 17 (AgNPs) which were evaluated for their antimicrobial effects after optimizing the pH of extract and 18 concentration of both extract and synthesized AgNPs. The characterization of synthesized AgNPs 19 was carried out using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…As shown in the data in Tables 1 and 2. This is in agreement with many studies; Samreen, Muzaffar, et al (2018) conducted a study on different bacterial strains, and the results indicated a significant inhibition of AgNPs compared to the absence of any inhibition for lemon extract (45). Furthermore, Mosae Selvakumar, Antonyraj, et al (2016), and Niluxsshun, Masilamani, et al (2021) discovered that lemon extract has slight activity while the zone of inhibition around AgNPs was significantly higher than the extract and controls and nearer to the inhibition of standard antibiotics (5,19).…”
Section: Anti-bacterial Effectiveness Of Silver Nanoparticlessupporting
confidence: 87%
See 1 more Smart Citation
“…As shown in the data in Tables 1 and 2. This is in agreement with many studies; Samreen, Muzaffar, et al (2018) conducted a study on different bacterial strains, and the results indicated a significant inhibition of AgNPs compared to the absence of any inhibition for lemon extract (45). Furthermore, Mosae Selvakumar, Antonyraj, et al (2016), and Niluxsshun, Masilamani, et al (2021) discovered that lemon extract has slight activity while the zone of inhibition around AgNPs was significantly higher than the extract and controls and nearer to the inhibition of standard antibiotics (5,19).…”
Section: Anti-bacterial Effectiveness Of Silver Nanoparticlessupporting
confidence: 87%
“…Although silver has anti-bacterial properties, lemon juice is rich in biologically active compounds such as flavonoids, carotenoids, and phenolic compounds, which act as natural antibiotics against pathogens in the body, such as bacteria (10,43). AgNPs differed significantly at p < 0.05 from lemon juice and AgNO3 (45). AgNPs have activity of silver NP derived from lemon juice showed enhancement in activity due to the synergistic effect of silver and biologically active compounds of lemon juice.…”
Section: Anti-bacterial Effectiveness Of Silver Nanoparticlesmentioning
confidence: 98%
“…Zinc oxide (ZnO) nanoparticles were synthesized with domestic waste potato peel after 24 h of incubation using starch present in the potato peel to reduce the metal ion [ 63 ]. Banana, pomegranate, lemon and orange peel extracts have also been found to possess the ability to reduce silver (Ag + ) ions in aqueous solutions to synthesize silver (Ag) nanoparticles [ 54 , 55 , 56 , 57 ]. Likewise, ZnO-NPs have been synthesized using tomato, grapefruit, lemon and orange peel [ 61 ].…”
Section: Fruit and Vegetable Peel-derived Metallic Nanoparticlesmentioning
confidence: 99%